Performance Evaluation of HTB-Based Bandwidth Management for Campus Networks Using MikroTik Routerboard - Sumarlin; Iscar Meriah Zai; Candra Irawan Batee; Naomi Rut M. Siboro; Tuboy Martin Gea; Hotma Mentalita (JCEIT: Journal of Computer Engineering and Information Technology, 2026)
The rapid growth of internet usage in campus environments, driven by academic, administrative, and digital learning activities, has led to significant increases in data traffic that can impact network performance and stability. At ITB Indonesia, the computer network relies on MikroTik RouterBoard as a core device for traffic management. However, during peak usage periods, network congestion may occur, necessitating a comprehensive performance analysis. This study aims to evaluate the performance of the MikroTik RouterBoard network in handling surges in data traffic within the ITB Indonesia campus. The research employs a quantitative experimental approach by simulating different traffic conditions, including normal and peak loads. Data were collected using monitoring tools integrated within the MikroTik system, focusing on key performance indicators such as throughput, latency, packet loss, and CPU utilization. The results indicate that the network performs efficiently under normal conditions, maintaining stable throughput and low latency. However, under high traffic loads, performance degradation is observed, including increased latency, higher CPU usage, and slight packet loss. The application of traffic management techniques, such as bandwidth allocation and load balancing, significantly enhances network performance. Therefore, MikroTik RouterBoard remains an effective solution when supported by proper optimization strategies. REFERENCES Adisetiawan, R. A. R. (2025). Transformation of Education in the Era of Digitalization Efforts Towards Technology-Based Education. Karapan Network Journal: Journal Computer Technology And Mobile Ad Hoc Network, 1(01). Aprelyani, S. (2025). Factors that affect network performance: signal quality and bandwidth. Greenation Journal of Engineering Sciences, 3(2), 85–92. Aritonang, M. A. S., & Simanullang, M. J. (2025). Application of a Network Monitoring System based on SNMP for early detection of network disturbances. Journal of Artificial Intelligence Technology Studies, 5(3), 735–742. Aulia, B. W., Rizki, M., Prindiyana, P., & Surgana, S. (2023). The crucial role of computer networks and databases in the digital era. Journal of Information Systems and Information Technology, 1(1), 9–20. Dachi, A. C., & Noprisson, H. (2025). Mikrotik Firewall Implementation Model In Traffic Management And Network Security. Jsai (Journal of Scientific And Applied Informatics), 8(3), 788–793. Dora Sandova, & Cahyo Prihantoro. (2021). Traffic Analysis on the LAN Network. Jsai: Journal of Scientific And Applied Informatics, 4(3), 329–337. Fitrian, H. P., Difa, D. H., Melianti, V. A., & Ramdhani, F. M. (2025). Analysis of factors that affect the performance of computer networks in a multi-user environment. Tamika: Journal of Informatics Management and Computerized Accounting, 5(2), 410–415. Kuncoro, W. A., & Santoso, L. (2025). Network Congestion Due to Social Media: Analyzing Its Impact on the Efficiency of Wireless Data Transmission. Scientific Journal of Information Systems, 4(2), 130–141. Nabawi, M., Permana, D. S., & Subekti, R. (2025). Design and implementation of internet connection management with load balancing and failover methods at Trans Coffee headquarters. National Journal of Informatics (Junif), 4(2), 1–13. Nasrullah, M. G., Heryana, N., & Solehudin, A. (2024). Bandwidth management uses the Token Bucket Hierarchical method on internet speed limiting. Jati (Student Journal of Informatics Engineering), 8(2), 2291–2296. Ndun, Y. J. (2025). The implementation of VLAN (Virtual Local Area Network) to improve the security and efficiency of the Dapodik application network at Oesusu Elementary School, Kupang Regency. Journal of Informatics and Applied Electrical Engineering, 13(3). Octavian, A. (2024). The redundancy network design uses the concept of etherchannel and hsrp with intervlan routing at Pln Uid Jakarta Raya. Journal of Informatics and Applied Electrical Engineering, 12(2). Pragasta, Y. (2025). Application of Load Balancing Technology on Mikrotik Routers with the Peer Connection Classifier Method. Digital Transformation Technology, 5(2), 131–140. Pramudito, T. D., Pranoto, W. J., & Hallim, A. (2025). Analysis of the quality of 4g LTE network services using the Walk Test method and Qos (Quality of Service) measurement at Samarinda Central Plaza. Pendas: Scientific Journal of Basic Education, 10(01), 341–360. Prasetio, D., Yuniar, R. O., Fahlewi, F., Agustina, D., Citra, E. J., & Rahman, A. (2025). Analysis of students' habits of using the internet to study at Baturaja University. Journal of Computer Innovation (Inokom), 1(3), 125–134. Prasetyo, F. H. P., Infitharina, E., & Febriyansyah, M. (2025). Application of the Network Development Life Cycle (NDLC) method in the development of computer networks. Journal Of Informatics And Communication Technology (JCT), 7(1), 80–87. Pratama, N. M. W. P., Fatchurrohman, F., & Susanto, I. B. (2024). Optimization of the internet network by using simple queue and microtik firewall at Malang City State Junior High School. Jati (Student Journal of Informatics Engineering), 8(6), 12828–12835. Rahman, T., Rafi, A. P., & Rifai, B. (2026). Implementation of VLAN on WLAN for optimization of enterprise network management. Technology, 20(1), 207–219. Rivaldi, K., & Purnama, G. (2025). Design and implementation of monitoring of computer network device infrastructure in data centers and informatics facilities through the application of Zabbik Network Engineering. Journal of Adijaya Multidisciplinary, 3(04), 589–611. Rizky, M. A. H., Solehudin, A., & Nurkifli, E. H. (2024). Bandwidth optimization on the internet network uses the simple queue and peer connection queue methods. Jati (Student Journal of Informatics Engineering), 8(4), 7856–7863. Subektiningsih, S., Renaldi, R., & Ferdiansyah, P. (2022). Comparative analysis of Tiphon Standard Qos parameters on wireless networks in the application of the PCQ method. Explore, 12(1), 57–63. Sufa, A. M., & Nasution, M. I. P. (2025). Perceptions and Barriers to the Use of Web-Based Academic Information Systems at the State Islamic University of North Sumatra. Scientific Journal of Economics, Management, Business and Accounting, 2(3), 347–357. Utomo, A. A. S., Supandi, S., & Rozzaqi, A. R. (2025). Analysis of wireless network performance based on Qos (throughput, delay, packet loss) parameters on variations in traffic during operational hours in users in the school environment at SMP Negeri 1 Ngaringan. Sibatik Journal: Scientific Journal of Social, Economic, Cultural, Technological, and Educational, 4(9), 2691–2970.